Annexin A1 subcellular expression in laryngeal squamous cell carcinoma - Alves, V. A. F.; Nonogaki, S.; Cury, P. M.; Wuensch-Filho, V.; de Carvalho, M. B.; Michaluart-Junior, P.; Moyses, R. A.; Curioni, O. A.; Figueiredo, D. L. A.; Scapulatempo-Neto, C.; Parra, E. R.; Polachini, G. M.; et al. (Wiley-Blackwell Publishing, Inc, 2008)
Annexin A1 (ANXA1) is a soluble cytoplasmic protein, moving to membranes when calcium levels are elevated. ANXA1 has also been shown to move to the nucleus or outside the cells, depending on tyrosine-kinase signalling, thus interfering in cytoskeletal organization and cell differentiation, mostly in inflammatory and neoplastic processes. The aim was to investigate subcellular patterns of immunohistochemical expression of ANXA1 in neoplastic and non-neoplastic samples from patients with laryngeal squamous cell carcinomas (LSCC), to elucidate the role of ANXA1 in laryngeal carcinogenesis.Serial analysis of gene expression experiments detected reduced expression of ANXA1 gene in LSCC compared with the corresponding non-neoplastic margins. Quantitative polymerase chain reaction confirmed ANXA1 low expression in 15 LSCC and eight matched normal samples. Thus, we investigated subcellular patterns of immunohistochemical expression of ANXA1 in 241 paraffin-embedded samples from 95 patients with LSCC. The results showed ANXA1 down-regulation in dysplastic, tumourous and metastatic lesions and provided evidence for the progressive migration of ANXA1 from the nucleus towards the membrane during laryngeal tumorigenesis.ANXA1 dysregulation was observed early in laryngeal carcinogenesis, in intra-epithelial neoplasms; it was not found related to prognostic parameters, such as nodal metastases.
Keywords: Annexin A1; head and neck neoplasm; Immunohistochemistry; laryngeal neoplasm